Prototipe Sistem Pemantauan Kondisi Cuaca Pekanbaru - Aulia Ikrar Muhammad; Emansa Hasri Putra (ABEC Indonesia, 2021)
The occurrence of differences in weather conditions (rain, temperature, humidity, wind direction and speed) in the city of Pekanbaru from one place to another even though it is still in one sub-district. The difference in rainfall can disturb the community. Many people do not know the information about the weather conditions. The application of technology in the form of sensors as a monitoring system for weather conditions can be used to assist in collecting information data for the local community. The design is made using Arduino which is equipped with an anemometer sensor that functions to measure wind speed, wind direction sensor, DHT11 temperature sensor to detect air temperature and humidity. The data that has been read by the sensor will be sent to the server which is displayed on the web. The data generated in the form of wind speed, wind direction, temperature, and humidity. The test results obtained that the tool can monitor weather conditions with a temperature range of 25oC to 33oC, the resulting temperature accuracy is 95.96%. The humidity accuracy value is 95.91%. The wind speed value generated by nature is 0.00 M/s when the wind conditions do not blow up to 3.05 M/s when the wind conditions blow, the accuracy value obtained from the wind speed sensor is 78.07%. The wind direction shown is northwest, west, southeast, and south. The wind direction when doing the test often shows the southeast cardinal direction. Monitoring is carried out via the internet via a web that is connected to the internet network. With this system, information on weather conditions can be known to everyone through the website in real time or directly to find out the current weather info Keywords: Monitoring Weather, Wind Speed ​​and Direction, Arduino, Website